Pengaruh Kuat Arus Dan Laju Alir Pada Pengolahan Air Payau Menjadi Air Bersih Dengan Metode Elektrokoagulasi Menggunakan Reaktor Listrik Kontinyu - Jhon Alperdo; Idral Amri; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Brackish water was a usual the result of saltwater intrusion to the groundwater. It is due to the environmental degradation. Brackish water containing high levels of metal pollution like Fe, Cl, Mn, Zn, etc. Brackish water also usually having high levels of TDS and pH values brackish water acidic.Therefore, brackish water should be treated first that fit for using as fresh water. Brackish water treatment plant run based on the electrocoagulation. This method has the potential to purify brackish water and decrease the metal content contained such as Fe without the addition of coagulants. The purpose of this study was to determine the application of electrocoagulation to be used to neutralize pH, and reduce levels of TDS and Fe on brackish water and also to determine the effect of changes in flow rate and current to neutralize pH, and reduce TDS and Fe levels in brackish water. The parameters tested included pH, TDS (Total Dissolved Solid), and Fe using AAS. The electrocoagulation process uses electrical power that flows in the direction of the electrode. The electrocoagulation reactor was paired with a cable connected to the power supply then connected to an electric current with variations currents (1,4 ;2 ; 2,6 A) and variations in flow rate (0,53 ; 1,15 ; 2,7 L/min). The results of this study found that the optimum conditions were obtained at current of 2,6 A and flow rates of 0,53L/min with increasing pH from 5,8 to 6,8, decreasing TDS from 480 to 295 mg/L, Fe decrease of 66,97% from 0,5971mg/L to 0,1972 mg/L. Therefore, based on the results of parameter being tested, brackish water processed with electrocoagulation using continuous electric reactor is in line with the portable water quality standards based on Permenkes RI No.492-2010.Keywords: Brackish water, current, electrocoagulation, flow rate